The impact of business networks on foreign subsidiaries development: Internationalizing by surfing on several global factories. Issue 3 (29th October 2018) - Baraldi, Enrico; Ciabuschi, Francesco; Lindahl, Olof; Perna, Andrea; Gregori, Gian Luca
Abstract : Purpose: The purpose of this paper is to explore two specific areas pertaining to industrial networks and international business (IB). First, the authors look at how business relationships influence the internationalization in time, from the establishment of the first subsidiary in a foreign market to the following ones, and in space, that is, across different markets. Second, the authors investigate how an increasing external network dependence of subsidiaries in their internationalization may cause a detachment of a subsidiary from the mother company as its knowledge becomes insufficient to guide a subsidiary's internationalization. Design/methodology/approach: This paper utilizes an exploratory, longitudinal, single-case study of Loccioni – a manufacturer of measuring and automatic control systems for industrial customers – to illustrate the specific dynamics of the influences of industrial networks on the internationalization of subsidiaries. Findings: The case study helps to elucidate the roles, entailing also free will and own initiative, of small suppliers' subsidiaries which operate inside several global factories, and how "surfing" on many different global factories, by means of several local subsidiaries, actually supports these suppliers' own international developments. This notion adds to our understanding of the global factory phenomenon a supplier focus that stresses how the role of suppliers is not merely that of being passive recipients of activities and directions from a focal orchestrating firm, but can also be that of initiative-takers themselves. Originality/value: The paper contributes to the IMP tradition by providing a multi-layered and geographically more fine-grained view of the network embedding companies that operate on internationalized markets. This paper thereby sheds light on a less investigated area of research within the IMP tradition: the link between internationalization in different countries and the interconnectedness between the industrial networks spanning these countries. At the same time, this paper contributes to IB theories by showing how a late-internationalizing SME can enter highly international markets by "plugging into" several established "Global Factories" as a way to exploit further opportunities for international expansion.